Profiles of Cortisol, Triiodothyronine, Thyroxine and Neutrophil/Lymphocyte Ratio as Stress Indicators in Swamp Buffaloes 15 Days Post-Transportation - H Maheshwari; . Yulnawati; A Esfandiari; . andriyanto; M D Andriani; A Khovifah (Faculty of Animal Science, Bogor Agricultural University, 2013)
Transportation may cause stress that affects livestock’s health. This research was conducted to observe the effect of transportation on the profiles of blood cortisol, triiodothyronine (T3), thyroxine (T4) and neutrophil/lymphocyte (N/L) ratio as stress indicators during 15 days post-transportation. Four females swamp buffaloes, 2-yr-old were used in this research. The animals were transported using an open truck, along 15 kilometers distance for 2 h. During acclimatization, the animals were fed grass twice a day and access to water ad libitum. Blood was collected at the time of arrival and everyday for 15 d post-transportation. Cortisol, T3 and T4were analyzed using Radioimmunoassay (RIA) method. Blood smears were also prepared and stained with Giemsa for leukocyte differential counts. Results showed a significant relation (P<0.05) between transport and an increase in cortisol and T4 level on day-1 post-transportation compared to the normal levels. The level of T3 was also increased on day-3 post-transportation. Total leukocyte counts were 8.91-18.83×10³/μL. Neutrophil, eosinophil, monocyte, and lymphocyte counts were 4.87-10.41×10³/μL, 0.66-1.75×10³/μL, 0.11-0.58×10³/μL, and 2.98-6.21×10³/μL, respectively. N/L ratio was 1.23-3.49 with >1.5 in average throughout the period of the research. It is concluded that transportation causes stress and therefore changes metabolic process.